Variation of water body in Dongting Lake from in situ measurements and MODIS observations in recent decades. Issue 8 (3rd August 2021) - Yang, Liu; Wang, Lunche; Zhang, Ming; Niu, Zigeng; Yao, Rui; Yu, Deqing; Li, Chang'an; He, Qiuhua
ABSTRACT: Identifying the spatiotemporal dynamics of the water body in Dongting Lake, the second largest freshwater lake in China, is crucial for water resource management. In this study, the variations of the water body were comprehensively analyzed based on remote sensing images and in situ measurements from 2000 to 2019. Four breakpoint detection approaches were integrated to analyze the change trends and explore the related driving forces behind the changes. The results showed that significant intra– and inter–annual fluctuations of the water body were found from 2000 to 2019. The water area and volume decreased at rates of 1.26 km 2 /a and 16.65 × 10 6  m 3 /a, respectively. During the entire study period, the outflow at Chenglingji station (CLJ), the inflow from three outlets of the Yangtze River (Inflow2), and the inundation conditions during the last period (Arealag ) made the largest relative contributions to the water area variation (around 25%, 27% and 24%, respectively). A breakpoint was detected around 2004, corresponding to the operation period of the Three Gorges Dam (TGD). The regulation of TGD profoundly affected the hydrological characteristics at the three outlets and CLJ, and may have indirectly caused the water area to expand by 2.41 km 2 /a during the dry seasons between 2004 and 2019. These results provide valuable insight into how natural and anthropogenic factors affect water body variation and may offer a practical reference for the local government to adjust management strategies.